Work-focused therapy in an internet-based CBT format – A mixed methods feasibility study - Henning Monsen; Jon Vøllestad; Peter Prescott; Audun Røren; Kristin Bruvik; Torkil Berge; Pål W. Wallace; Tine Nordgreen; Nick Titov; Anders Hovland (Internet Interventions, 2025)
Background: Common mental disorders (CMD) are one of the main causes for work absenteeism. While traditional cognitive behavioural therapy is effective for symptom reduction, its impact on return to work is less pronounced. Work-focused therapy for those with CMD has shown positive results on return to work, but availability of such treatment is scarce. Objective: To investigate a transdiagnostic work-focused Internet Delivered Cognitive Behavioural Therapy (W-ICBT) intervention. Further, to investigate its feasibility in terms of use and adherence, including the participants experience of perceived effects, for outpatients on sick leave with diagnoses of depression and/or anxiety. Method: We conducted a naturalistic feasibility study using a convergent, mixed-methods pre-post design. Outcomes included adherence and use of the treatment, return to work, work related self-efficacy, symptoms of depression and anxiety, quality of life and the experience of participants through qualitative interviews. Results: 19 patients were screened, 15 included and 11 completed the 12-week treatment. Degree of sick leave was reduced from 79 % to 32 % for the completer sample (g = 0.95, p = .003), with statistically significant results on self-efficacy (g = 1.05 p = .005), depression (g = 0.81, p = .024), quality of life (g = 1.20, p = .002). No significant changes were observed on measures of anxiety and impairment of daily living. These results were supported by the findings from the qualitative interviews. Conclusion: W-ICBT appears to be a promising approach to reducing work absenteeism and warrants further research.